ChemInform Abstract: Boundary Engineering for the Thermoelectric Performance of Bulk Alloys Based on Bismuth Telluride. Issue 36 (September 2015) - Mun, Hyeona; Choi, Soon‐Mok; Lee, Kyu Hyoung; Kim, Sung Wng
Abstract Review: 148 refs.